Speed Control of Induction Motor on C2000 DSP Platform - Quang, Nguyen Hong (Review of Information Engineering and Applications, 2019)
Three-phase AC motors are widely used in the industry. Nowadays, it accounts for 90% of the motors used in engine applications in technological lines. Control methods for this object are also quite complete and installed in industrial inverters in commerce. For commercial equipment, operators must not interfere with the control structure due to the closed nature of the system. For small-scale applications and applications that require operators, it is necessary to intervene in the control structure to customize the technology process. However, it cannot be done with commercially available equipment. Therefore, the authors propose a solution to build a standardized hardware system that can interfere with the control structure using the C2000 family microcontroller. The advantage of this solution is that it is inexpensive and allows us to install different algorithms. Besides, it is possible to connect to PC via Matlab/Simulink in real-time control problem.